A Christianson syndrome-linked deletion mutation (∆287ES288) in SLC9A6 disrupts recycling endosomal function and elicits neurodegeneration and cell death. Issue 1 (December 2016) - Ilie, Alina; Gao, Andy; Reid, Jonathan; Boucher, Annie; McEwan, Cassandra; Barrière, Hervé; Lukacs, Gergely; McKinney, R.; Orlowski, John
Abstract Background Christianson Syndrome, a recently identified X-linked neurodevelopmental disorder, is caused by mutations in the human gene SLC9A6 encoding the recycling endosomal alkali cation/proton exchanger NHE6. The patients have pronounced limitations in cognitive ability, motor skills and adaptive behaviour. However, the mechanistic basis for this disorder is poorly understood as few of the more than 20 mutations identified thus far have been studied in detail. Methods Here, we examined the molecular and cellular consequences of a 6 base-pair deletion of amino acids Glu287 and Ser288 (∆ES) in the predicted seventh transmembrane helix of human NHE6 expressed in established cell lines (CHO/AP-1, HeLa and neuroblastoma SH-SY5Y) and primary cultures of mouse hippocampal neurons by measuring levels of protein expression, stability, membrane trafficking, endosomal function and cell viability. Results In the cell lines, immunoblot analyses showed that the nascent mutant protein was properly synthesized and assembled as a homodimer, but its oligosaccharide maturation and half-life were markedly reduced compared to wild-type (WT) and correlated with enhanced ubiquitination leading to both proteasomal and lysosomal degradation. Despite this instability, a measurable fraction of the transporter was correctly sorted to the plasma membrane. However, the rates of clathrin-mediated endocytosis of the ∆ES mutant as well as uptake of companion vesicular cargo, such as the ligand-bound transferrin receptor, were significantly reduced and correlated with excessive endosomal acidification. Notably, ectopic expression of ∆ES but not WT induced apoptosis when examined in AP-1 cells. Similarly, in transfected primary cultures of mouse hippocampal neurons, membrane trafficking of the ∆ES mutant was impaired and elicited marked reductions in total dendritic length, area and arborization, and triggered apoptotic cell death. Conclusions These results suggest that loss-of-function mutations in NHE6 disrupt recycling endosomal function and trafficking of cargo which ultimately leads to neuronal degeneration and cell death in Christianson Syndrome.